Fuzzy decision model in context-aware B2B collaboration - Ma, Wen Yan (2010)
This project aims to validate and improve the fuzzy model in the Business-to-Business collaboration software Cognitive Advisor. Towards this goal, extensive tests have been carried out to ensure that the system is properly implemented, and several methods have been proposed and implemented to improve the fuzzy-model’s performance. Using the Analytical Hierarchic Process technology and refined fuzzy techniques, the system ranks the suppliers over linguistically described and vague criteria, provides confident results over combination of imprecise and numerical decisive factors, reflects the relationship of relative importance among the selected criteria in the final evaluation scores and presents more discernible values in the final stage of the fuzzy model. The system will provide more valuable partner matching if it could be refined and further enhanced with other fuzzy methodologies or more powerful decision making algorithms.